Synthesis and Local Probe Gating of a Monolayer Metal‐Organic Framework. (22nd March 2021) - Yan, Linghao; Silveira, Orlando J.; Alldritt, Benjamin; Krejčí, Ondřej; Foster, Adam S.; Liljeroth, Peter
Abstract: Achieving large‐area uniform 2D metal‐organic frameworks (MOFs) and controlling their electronic properties on inert surfaces is a big step toward future applications in electronic devices. Here a 2D monolayer Cu‐dicyanoanthracene MOF with long‐range order is successfully fabricated on an epitaxial graphene surface. Its structural and electronic properties are studied by low‐temperature scanning tunneling microscopy and spectroscopy complemented by density‐functional theory calculations. Access to multiple molecular charge states in the 2D MOF is demonstrated using tip‐induced local electric fields. It is expected that a similar strategy could be applied to fabricate and characterize 2D MOFs with exotic, engineered electronic states. Abstract : The structural and electronic properties of a 2D monolayer Cu‐dicyanoanthracene (DCA) metal‐organic framework (MOF) on an epitaxial graphene substrate are studied using complementary experimental and theoretical techniques. The 2D Cu‐DCA MOF possesses a kagome band structure near the Fermi level. Access to multiple molecular charge states in the 2D MOF is demonstrated using the tip‐induced local electric fields.